Bivanjsko nelagodje žensk kot tematsko osišče pripovedne proze Jasne Jurečič - Smotlak, Maja (Jezik in slovstvo, 2016)
Jasna Jurečič (1955-2014) was a writer who moved from her hometown of Zadar to Ljubljana, and from there to Sales near Trieste, where she conceived and realised her literary works. For this reason, she is legitimately considered to be a Slovenian author from Italy as well as a contemporary Slovenian female author. Her writing pivots around women and their feeling of existential unease, which can have various forms, origins and responses. Through an analysis of these elements, the article presents an overview of all of Jasna Jurečič's published prose. It is the first presentation of this author, who was unable to establish herself fully in the Slovenian literary world because of her premature death. Her prose has not previously been the subject of a comprehensive review and thorough research within the context of Slovenian literary studies.
Keywords: Jurečič, Jasna, 1955-2014; slovenski romani; slovenska kratka proza; slovenska književnost v Italiji; ženski liki; literarne teme; literarne študije